2018
DOI: 10.7717/peerj.5822
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of microarray datasets identify several chromosome segregation-related cancer/testis genes potentially contributing to anaplastic thyroid carcinoma

Abstract: AimAnaplastic thyroid carcinoma (ATC) is the most lethal thyroid malignancy. Identification of novel drug targets is urgently needed.Materials & MethodsWe re-analyzed several GEO datasets by systematic retrieval and data merging. Differentially expressed genes (DEGs) were filtered out. We also performed pathway enrichment analysis to interpret the data. We predicted key genes based on protein–protein interaction networks, weighted gene co-expression network analysis and genes’ cancer/testis expression pattern.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
(96 reference statements)
2
6
0
Order By: Relevance
“…High KIF2C expression in male patients with esophageal squamous cell carcinoma is associated with worse overall survival, and even with the same pathological TNM stage, patients with high KIF2C expression had a worse outcome (43). Similar results have indicated that KIF2C promotes breast cancer, prostate cancer, and thyroid carcinoma (44)(45)(46). In our study, KIF2C was also upregulated in HCC tissues and was associated with a poor outcome.…”
Section: Discussionsupporting
confidence: 81%
“…High KIF2C expression in male patients with esophageal squamous cell carcinoma is associated with worse overall survival, and even with the same pathological TNM stage, patients with high KIF2C expression had a worse outcome (43). Similar results have indicated that KIF2C promotes breast cancer, prostate cancer, and thyroid carcinoma (44)(45)(46). In our study, KIF2C was also upregulated in HCC tissues and was associated with a poor outcome.…”
Section: Discussionsupporting
confidence: 81%
“…The results showed that high levels of ANLN, CENPF, KIF2C, TPX2, and NDC80 indicated poor prognosis in ATC, suggesting that intervention of these genes might be a promising strategy for ATC treatment. Liu's meta-analysis of microarray datasets identified TRIP13, DLGAP5, HJURP, CDKN3, NEK2, KIF15, TTK, KIF2C, AURKA and TPX2 as cell cycle-related key genes potentially contributing to anaplastic thyroid carcinoma, 34 which were in consistence with some of our results (KIF2C, TPX2).…”
Section: Discussionsupporting
confidence: 90%
“…By constructing a gene co-expression network and identifying related gene clusters, the correlation between gene modules and phenotypes can be calculated based on phenotypic information, and the most relevant gene modules can be found. Numerous potential biomarkers have been identified to date based on WGCNA for sequencing data [14][15][16]. For example, Tang et al identified five genes as prognostic biomarkers for breast cancer, and Qiu et al revealed several genes associated with the development of breast cancer for further basic and clinical research [14,17].…”
Section: Introductionmentioning
confidence: 99%